IMPLEMENTATION OF GOVERNMENT POLICIES IN WASTE MANAGEMENT IN BITU NG CITY - Senny Enggelina Manansang; Jetty E.H. Mokat; Joyce Ch. Kumaat (PT. Radja Intercontinental Publishing, 2026)
Abstract This study aims to analyze the implementation of waste management in Bitung City based on Regional Regulation Number 17 of 2013 and identify the factors that influence it. This study uses a descriptive qualitative approach with the Miles and Huberman interactive analysis model. Data were collected through in-depth interviews, field observations, and documentation. Informants consisted of officials and staff of the Bitung City Environmental Service, village/district officials, cleaning staff/waste collectors, and the community. The results of the study indicate that the implementation of waste management is not optimal in three main indicators: (1) Waste sorting is still very limited because the community is not used to it, supporting facilities are not available, and the perception is that sorted waste will be mixed again during transportation; (2) Waste collection faces problems with the availability of very limited TPS (landfills), the condition of the TPS does not meet the standards of being closed, neat, and odorless, and the collection mechanism is not systematic; (3) Waste transportation is disrupted because the fleet is often damaged due to lack of routine maintenance, reactive (emergency) maintenance, uneven schedules and routes, and the absence of a special fleet for sorted waste so that sorted waste is mixed again. Factors that influence implementation include internal bureaucratic factors (limited personnel, poor fleet maintenance, weak coordination), social and cultural factors (habits of littering, sorting not yet a culture, weak social sanctions), as well as policy and institutional factors (weak enforcement of sanctions, no special institutions at the sub-district level, budget limitations).